Macropinocytosis: New Insights Into Its Underappreciated Role in Innate Immune Cell Surveillance - Canton, Johnathan (Frontiers in Immunology, 2018)
Macropinocytosis has received increasing attention in recent years for its various roles in nutrient acquisition, immune surveillance and virus and cancer pathologies. In most cases macropinocytosis is initiated by the sudden increase in an external stimulus such as a growth factor. This ‘induced’ form of macropinocytosis has been the subject of much of the work addressing its mechanism and function over the years. An alternative, ‘consitutive’ form of macropinocytosis restricted to primary innate immune cells also exists, although its mechanism has remained severely understudied. This mini-review focuses on the very recent advances that have shed new light on the initiation, formation and functional relevance of constitutive macropinocytosis in primary innate immune cells. An emphasis is placed on how this new understanding of constitutive macropinocytosis is helping to define the sentinel function of innate immune cells including polarized macrophages and dendritic cells.